Northern Lights: The University of Durham and William Weightman. (2nd October 2015) - Gamble, Bob
Abstract : In September 1831, the gathering clouds over the Established Church persuaded the wealthy and powerful See in Durham to instigate a process that was to lead to the creation of the first university in the North of England. The Reverend William Weightman was one of the University of Durham's first alumni, achieving a Licentiate in Theology. What were the influences and experiences that this highly educated young clergyman carried with him from Durham when he became a curate at Haworth in 1839? How had the turbulent English religious climate of the 1830s shaped him? This paper examines William's privileged position as one of the early precious products of Durham's important new theological project, one of the very first Northern Lights sent to shine over the 'bogs and mountains', and shows how this context may give us a greater understanding of related events in the Brontë canon. 1